Grid-Following Voltage Source Converters: Basic Schemes and Current Control Techniques to Operate With Unbalanced Voltage Conditions - Pablo Montero-Robina (IEEE, 2021)
The growing relevance of voltage source converters (VSCs), and the deep impact they have on the development and maintenance of the electrical grid, increase the necessity of further research on how to deal with nonideal grid conditions from the VSCs control. This paper is aimed to summarize the basic techniques and schemes that might be required for a grid-connected VSC to work under these conditions: grid synchronization schemes, sequence decomposition, current reference generation, and current controllers. At the same time, some alternative schemes that improves the basic ones are cited. Modelling and the two typical current controllers design and tuning under stationary and synchronous reference frames are also exhibited. Given the importance of the current control stage in the VSC behaviour, five control schemes, designed to track negative sequence currents, are shown and tested in simulation and experiments. According to the experiments, it is shown that the standard proportional-resonant controller achieves the best performance in negative sequence tracking due to the robustness of its non-ideal version, the improved implementation thanks to the delta operator, and the non-dependence on grid-synchronization schemes. Alternatively, one approach based on dual synchronous reference frame is also highlighted for easiness of implementation and good performance.